2004
DOI: 10.1038/nbt1012
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of sequence-dependent and mutational effects on the aggregation of peptides and proteins

Abstract: We have developed a statistical mechanics algorithm, TANGO, to predict protein aggregation. TANGO is based on the physico-chemical principles of beta-sheet formation, extended by the assumption that the core regions of an aggregate are fully buried. Our algorithm accurately predicts the aggregation of a data set of 179 peptides compiled from the literature as well as of a new set of 71 peptides derived from human disease-related proteins, including prion protein, lysozyme and beta2-microglobulin. TANGO also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
1,610
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,522 publications
(1,659 citation statements)
references
References 26 publications
40
1,610
3
6
Order By: Relevance
“…We cannot, of course, exclude the possibility that our ancestral sequences contain biases or errors that are undetectable from sequence analysis but still impactful. Similarly, we analysed our LeuB sequences for their aggregation potential (using TANGO;Fernandez-Escamilla et al 2004) and, again, found no trend with inferred evolutionary age. All of our LeuBs are predicted to have a low average percentage aggregation per residue (\2 %) and, in fact, BCVX contains the greatest number of aggregation-prone residues and aggregation-prone stretches.…”
Section: In Vivo Fitness Is Not Correlated With Stability or Catalytimentioning
confidence: 86%
“…We cannot, of course, exclude the possibility that our ancestral sequences contain biases or errors that are undetectable from sequence analysis but still impactful. Similarly, we analysed our LeuB sequences for their aggregation potential (using TANGO;Fernandez-Escamilla et al 2004) and, again, found no trend with inferred evolutionary age. All of our LeuBs are predicted to have a low average percentage aggregation per residue (\2 %) and, in fact, BCVX contains the greatest number of aggregation-prone residues and aggregation-prone stretches.…”
Section: In Vivo Fitness Is Not Correlated With Stability or Catalytimentioning
confidence: 86%
“…Considerable attention has been devoted to exploring the nature and origin of such disorders from a structural viewpoint and to understanding the manner in which the balance between normal and aberrant conformational transitions can be perturbed. 20 Several studies have involved in vitro studies coupled with computer simulations, [20][21][22][23] and many others have been concerned with the goal of relating processes studied in atomic detail in the test tube to their quantitative effects in living systems. [24][25][26] Moreover, recent findings suggest that further developments in this area could have much more general relevance to understanding the way in which well-established physical and chemical principles can provide new insights into the apparent complexity of biology.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional all-atom molecular dynamics simulations have been carried out to model the aggregation of disease-related peptides such as Aβ and polyglutamine [235][236][237]. Other techniques seek to identify which parts within larger proteins are responsible for their aggregation behavior, resulting in the identification of sequence stretches in various proteins that are "amyloidogenic," or "hot spots" for aggregation [238][239][240]. Underlying this work is the idea that evolution acts to prevent aggregation by burying aggregation-prone protein sequences or otherwise prohibiting their apposition in protein structures and during folding 1 .…”
Section: Protein Self-association and Aggregationmentioning
confidence: 99%